2018
DOI: 10.1097/jom.0000000000001346
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and Benzodiazepine Use Before Injury Among Workers in Washington State, 2012 to 2015

Abstract: Pre-injury opioid and benzodiazepine use may increase the risk of disability after work-related injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Such psychological factors therefore represent shared predictive factors for both opioid use and disability among patients with low back pain . Pre‐injury use of opioids has also been associated with an increased risk of a workers’ compensation claim . In our study, we do not have data to determine whether opioids were initiated before or after the date of injury.…”
Section: Discussionmentioning
confidence: 93%
“…Such psychological factors therefore represent shared predictive factors for both opioid use and disability among patients with low back pain . Pre‐injury use of opioids has also been associated with an increased risk of a workers’ compensation claim . In our study, we do not have data to determine whether opioids were initiated before or after the date of injury.…”
Section: Discussionmentioning
confidence: 93%
“…These can be powerful predictors of mortality, but others were notably missing, including preinjury smoking, alcohol and drug consumption, body mass index, and underlying diseases. Researchers have reported that both individual health and behavioral as well as work‐related factors may influence the risk of occupational injury . In order for these unmeasured factors to act as confounders and explain away the observed associations, they would need to precede the initial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Van Hasselt et al 28 showed that after adjustment for covariates, workers who reported prescription drug misuse within the past month had a 7.4% increase in probability of being absent from work one or more days during the previous month. Using workers' compensation claims in Washington State from 2012 to 2015, Nkyekyer et al 29 showed that pre-injury opioid and benzodiazepine use may increase the risk of disability after work-related injury. Thumula et al 30 and O'Hara et al 31 conducted studies similar to ours, but their scope was limited to workers who used the workers' compensation system and did not have information on sociodemographic factors that may be associated with opioid use in workers.…”
Section: Discussionmentioning
confidence: 99%